Kvinnen og havet: Vigdis Stokkeliens apokalyptiske 1970-tallsromaner i lys av Blue humanities - Hamm, Christine (Passage - Tidsskrift for litteratur og kritik, 2025)
“Women and the Sea: Vigdis Stokkelien’s Apocalyptic Novels from the 1970s and Blue Humanities” In the two novels Sommeren på heden [Summer on the heath] (1970) and Lille-Gi- braltar [Little-Gibraltar] (1972), Norwegian writer Vigdis Stokkelien explores how women relate to the sea. She shows how capitalism and militarism violate both na- ture and the female body. Stokkelien’s stylistic devices create the effect of a subma- rine temporality thatreveals the protagonists as entangled, something that simulta- neously provokes the need for liberation.